STUDI KASUS TENTANG SISWI YANG MEMILIKI KEPRIBADIAN MASKULIN DI KELAS XI SMA NEGERI 9 PONTIANAK TAHUN 2016 - Rismawati, Rismawati; Yuline, Yuline; Lestari, Sri (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
Abstract Personality is the character of a person who is seen through his behavior as a whole so that it describes a specific and consistent personal identity. Masculine is the inherent nature of men describing the condition of men who tend to be free, aggressive, and emotional. Students who have masculine personalities are female students who have the nature and appearance of men who are not necessarily owned by women. General research problem: "How do you deal with female students who have masculine personalities?" The sub problem is: (1) What are the characteristics of female students who have masculine personalities? (2) What are the factors that cause female students to have masculine personalities? (3) What are the relief efforts that can be done to overcome female students who have masculine personalities?The method used in this study is a descriptive method, with a form of case study research. Using 2 case subjects and the techniques used are interviews, observation and home visits. The data collection tool is an observation guide. The subject matter in this study were 2 case subjects. The general conclusion is the effort to overcome female students who have masculine personality in class XI Pontianak 9 SMA Negeri uses two counseling models namely behavioral counseling model and rational emotive counseling therapy model. Suggestions for case I subjects and case subject II are expected to continue to carry out the alternative assistance that has been given.Â Keywords: Efforts, Students, Masculine Personality.